ANALISIS MAKNA PUISI “DERAI-DERAI CEMARA” KARYA CHAIRIL ANWAR - Nisa Rasasti; Teti Sobari (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2021)
The poetry made by Chairil Anwar entitled "Derai-Derai Cemara" has a very beautiful word and hides a million meanings. Poetry has a thousand meanings when the reader reads, depending on the reader's interpretation. Because the reader has different thoughts and interpretations. Readers also often have difficulty understanding the meaning in the poems they read. Therefore, the aim of this poem-reviewing is to equalize the thoughts and interpretations of every reader, thus it could make the reader easier to read this one of Chairil Anwar's poetry. In this study, researchers used qualitative descriptive method, where this study present the results of the study with clear and simple words so that the the reader does not have difficulty in undersanding it. His poetry could make the readers feel the sorrows and the pain in every word. This poetry conveys the process of human life journey is not easy and not up to expectations he has, which eventually leads them to surrender to destiny and realize that death is the end of everything.